Relationships between perceived exertion and physiological variables during swimming - Ueda, T.; Kurokawa, T. (International Journal of Sports Medicine, 1995)
Male (N = 7) and female (N = 10) Ss performed tethered swimming at five different submaximal intensities. Perceived exertion was measured on a category scale (RPE) using purely verbal descriptions, and a category-ratio scale (CR-10) using both verbal and numerical descriptors. Physiological variables were: VO2, HR, and HLa. Drag in the tether was an independent variable. Results: Drag was related linearly with VO2 in both males and females. HR was related linearly with drag and VO2 in both males and females. HLa was related exponentially with both drag and VO2 in both groups. RPE increased linearly with drag in both males and females. However, CR-10 increased exponentially. Implication: Since HR declines with age, RPE can be used to measure exertion independent of age. It has greater utility for prescribing work intensities for swimmers of all ages than the currently popular HR ranges.